Transport pathway and depocenter of anthropogenic heavy metals off the Shandong Peninsula, China - Xu, G.; Liu, Jian; Pei, S.; Gao, M.; Kong, X. (Academic Press, 2016)
© 2016 Surface sediment grain size as well as the spatial distribution, sources and geochemical baseline levels of heavy metals in the south Shandong Peninsula clinoform were analyzed to determine the transport pathway and main depocenter of anthropogenic heavy metals off the peninsula. Results showed that the surface sediments were primarily silt-sized components, and the fine grain matter mainly originated from the Yellow River and rivers around Laizhou Bay. Heavy metals Cu, Pb, Zn, Cr, and Cd were predominantly from natural sources and their spatial distributions were controlled by grain size; conversely, anthropogenic As (concentration above geochemical baseline level 10.9 mg/kg) was principally derived from human activities, and its transportation from the Yellow River and Laizhou Bay was controlled by the Shandong Coastal Current off the Shandong Peninsula. Furthermore, the anthropogenic As was deposited in three main areas, that is, the Yellow River estuary, Laizhou Bay, and south Shandong Peninsula clinoform.